Arduino for developing problem-solving and computing competencies in children - Vidal Silva, Cristian.; Jiménez Quintana, Claudia.; Madariaga García, Erika. (Science and Information Organization, 2022)
Fostering children’s problem-solving and computational programming competencies is crucial at the current time. Like in other in-developing nations, children grew up with technology in Chile. Developing programming and problem-solving competencies in children seems a reachable task using high-level block-based programming languages. However, programming and electronics competencies often emerge at higher educational levels. This article presents that using Arduino can enhance the development of programming and problem-solving competencies in children and encourages them to think in new ways. This article uses TinkerCAD, an online emulator of Arduino, to teach fundamental electronic circuits and computer programming components. Using TinkerCAD effectively addresses various computing and electrical difficulties, such as turning on and off a group of lights and reading sensors to respond to the acquired values. This article seeks to develop problem-solving and computer programming competencies in primary school students, given the significance of both competencies, the open nature of Arduino, and the applicability of TinkerCAD, which permits using a block-based programming language. Children that took part in the trial saw an increase in their academic performance on average, which is a critical concomitant finding. The essential drawbacks of this project were the children’s lack of knowledge of electronics and programming principles and the need to use a computer with an internet connection.
Keywords: Arduino - Niños; Competencies; Problemsolving; Programación